A new enzymatic immobilization carrier based on graphene capsule for hydrogen peroxide biosensors. (1st January 2015) - Fan, Zengjie; Lin, Qianqian; Gong, Peiwei; Liu, Bin; Wang, Jinqing; Yang, Shengrong
Graphical abstract: Abstract: Enzymatic loss and inactivation are two main problems which can affect the performance of the biosensor. In order to resolve these two problems, a new kind of enzymatic biosensor for the amperometric detection of hydrogen peroxide (H2 O2 ) was developed using biomimetic graphene capsules (GRCAPS). Horseradish peroxidase was initially encapsulated in GRCAPS using porous CaCO3 as sacrificial templates to mimic the existence form of bio-enzymes in the organisms, and then GRCAPS and graphene-poly(sodium 4-styrenesulfonate) were alternatively assembled onto the substrate of indium tin oxide for constructing multilayer films of the biosensor. Transmittance electron microscopy and field-emission scanning electron microscopy analyses proved that the GRCAPS and multilayer films were prepared. Electrochemical experiment results indicated that easy, direct electrochemistry and good catalytic activity toward H2 O2 oxidation can be achieved with this biosensor. The resulting biosensor presented a wide linear range of 0.01–12 mmol l −1, a low detection limit of 3.3 μmol l −1 (S/N = 3), excellent anti-interference ability, and long-term stability as well.